Lentinan modulates intestinal microbiota and enhances barrier integrity in a piglet model challenged with lipopolysaccharide. Issue 1 (14th January 2019) - Wang, Xiuying; Wang, Wenjun; Wang, Longmei; Yu, Cheng; Zhang, Guolong; Zhu, Huiling; Wang, Chunwei; Zhao, Shengjun; Hu, Chien-An Andy; Liu, Yulan
Abstract : The protective effects of lentinan may be associated with inhibition of inflammation, production of SCFAs, and alterations of microbiota composition. Abstract : The intestinal microbiota plays a vital role in metabolism, pathogen resistance, and immune development in host cells, and is modifiable by dietary change. Lentinan (LNT), a type of mushroom polysaccharide, is known to ameliorate intestinal inflammation with the potential of therapeutic effect on digestive diseases. We hypothesized that LNT could alleviate Escherichia coli lipopolysaccharide (LPS)-induced intestinal injury via regulating the composition and metabolites of intestinal microbiota in a piglet model. Twenty-four weaned piglets were used in a 2 × 2 factorial design, and the main factors included a dietary treatment (basal or LNT diet) and immunological challenge (LPS or saline). After feeding basal or LNT diet for 21 days, pigs were injected with LPS or saline. At 4 h post-injection, pigs were killed and jejunum, ileum and cecal digesta were collected. LNT improved intestinal morphology and barrier function. LNT also inhibited inflammatory signaling pathways (toll-like receptor 4 and nucleotide binding oligomerization domain protein) and pro-inflammatory cytokines (tumor necrosis factor-α, interleukin-1β and interleukin-6) expression, as well as up-regulated the heat shock protein 70 expression in small intestine. In addition, LNT enhanced the concentrations of propionate, butyrate, isobutyrate and isovalerate in cecal digesta, resulting in a significant increase in histone acetylation without affecting the protein level of G protein-coupled receptor 41 (GPR41), a short chain fatty acid receptor. Bacterial 16S rRNA gene pyrosequencing showed that LNT had a great impact on gut microbiota composition at different taxonomic levels. Moreover, the correlation analysis revealed some potential relationships between cecal metabolites and certain intestinal microbiota. These results indicate that LNT promotes intestinal health, in part, through altering intestinal microbiota composition and increasing the short chain fatty acid synthesis, which subsequently lead to a reduction in inflammation and hyper-acetylation of histones.